Interactive Audio-Visual Digital Books in Reading Corners to Increase Early Childhood Interest and Literacy - Retno Tri Widayati; Farida Nugrahani; Suwarto (Universitas Pendidikan Ganesha, 2026)
Low reading interest among early childhood students remains a challenge in implementing the School Literacy Movement. Limited interesting reading materials and suboptimal use of technology make children less enthusiastic about reading. This study aims to develop and analyze the feasibility, practicality, and effectiveness of audio-visual-based interactive digital books in reading corners to improve early childhood literacy skills. This is qualitative research. The subjects involved in this study were elementary school students. The method used is Research and Development (R&D) with the ADDIE model. Data were obtained through observation, questionnaires, and interviews involving media experts, material experts, teachers, and students. The data sources in this study include both primary and secondary data. Data collection techniques used questionnaires and observations. Quantitative data analysis uses a percentage formula to determine the level of feasibility. The main results of the study indicate that the use of audio-visual interactive digital books in reading corners is effective in increasing interest and literacy skills among early childhood students. Children appear more enthusiastic about participating in reading activities, as indicated by increased visits to the reading corner and active involvement during reading. This study concludes that interactive digital books in reading corners are feasible, practical, and effective as an innovative medium for improving early childhood literacy. The implications of this research emphasize the importance of using innovative, adaptive learning media to enhance early childhood interest and literacy.